THE USE OF VIDEO TO DEVELOP SPEAKING SKILLS FOR INTERMEDIATE-LEVEL STUDENTS AT MESKOMAMBAN SCHOOL - Dwi Kurniawan; Nur Cholis Agus Santoso; Nasaruddin Nasaruddin (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
This study aims to explore the development of speaking skills through the use of video at Meskomamban Junior High School. The researcher observed that the teaching methods employed there were not innovative, rather stagnant, and lacked sufficient teaching aids, leading to decreased enthusiasm and diligence among students. In response to these issues, the study was conducted in a quasi-experimental manner by utilizing video as a medium to enhance speaking skills. The researcher played a dual role in order to assess the effectiveness of using videos to improve the speaking abilities of ninth-grade students at Meskomamban Junior High School, as well as to evaluate the advancement of instructional media in the school. The research focused specifically on the application of video as a teaching tool. The study population consisted of ninth-grade students. Data collection was carried out through testing, with both quantitative and qualitative analysis methods used. The results showed that the use of video media significantly improved students’ Arabic speaking skills, as reflected in the test scores at each stage: prior to the intervention, the score was 32%; in the first phase, it increased to 58%; and in the second phase, it further rose to 83%. These findings indicate a notable enhancement in Arabic speaking proficiency.